Measuring Level of Motoric Ability Utilizing Bocce Ball for Children with Mild Mentally Disabled - Kresnapati, Pandu; Fatkhu Royana, Ibnu; Setyawan, Danang Aji (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
Adaptive physical education is designed for children with disabilities. The school system, learning strategies, and the overall school environment need to be prepared to overcome the challenges faced by children with disabilities. The main obstacle in learning adaptive physical education is the low enthusiasm of children during the learning process. This research used a quantitative descriptive approach. The primary variable is the ability of children with mild mental disabilities to throw the ball at the bocce game. The research subject is 26 mentally disabled students, consisting of 16 males and 10 females. Data analysis techniques using descriptive statistical techniques using percentages. The study's results reveal that Post-intervention results indicate a notable improvement in gross motor skills. The intervention significantly enhanced the gross motor skills of male students, with 81.25% achieving